kepemimpinan pedagogis Pedagogical Leadership of Kindergarten Principals in Kendal Regency - Novita Indarni; Deasylina Da Ary; Edi Waluyo; Ali Formen (Universitas Pendidikan Ganesha, 2025)
Pedagogical leadership plays a crucial role in creating a learning environment that supports optimal early childhood development. However, the implementation of pedagogical leadership by school principals in early childhood education institutions still shows variations in both understanding and practice. This study aims to analyze and evaluate the pedagogical leadership practices of kindergarten principals and to assess their effectiveness in supporting instructional management and school organizational processes. The study employed a quantitative approach using a descriptive survey design. The participants consisted of 102 kindergarten teachers selected through proportional random sampling, with the criterion of having at least one year of teaching experience in the same institution. Data were collected using a closed-ended questionnaire developed based on pedagogical leadership indicators and supported by documentation. The data were analyzed using descriptive quantitative analysis through percentage statistics to describe the level of pedagogical leadership implementation. The results indicate that school principals have implemented pedagogical leadership at a good level, particularly in aspects of structural and functional organizational management, equitable task distribution, and the implementation of periodic performance evaluations. These findings suggest that principals act as instructional leaders who are able to integrate pedagogical vision with adaptive managerial practices. This study implies the importance of strengthening principals’ pedagogical leadership competencies to enhance instructional management and organizational effectiveness in early childhood education institutions.